(untitled) (The Peerian Journal, 2024)
The integration of technology in education has the potential to enhance the development of visual and creative competencies among future educators. In this scientific article, we explore the role of technology in fostering the visual and creative skills necessary for effective teaching and learning. We discuss various technological tools and approaches that can be utilized to support the development of these competencies among aspiring educators. Furthermore, we highlight the benefits and challenges associated with incorporating technology into teacher education programs. By leveraging technology, educational institutions can prepare future educators to effectively engage students in visual and creative learning experiences